Primary chondrosarcoma of bone: a clinicopathological and oncological outcome analysis - Subbiah, S.; D., Priya (International Journal of Research in Orthopaedics, 2024)
Chondrosarcomas are a heterogenous group of cartilaginous matrix-producing malignant neoplasms. They have varied morphological features and different clinical behaviors. The tumors usually range from benign low-grade tumors or intermediate atypical cartilaginous tumors (ACTs), to malignant, aggressive high-grade tumors. A multidisciplinary team at a tertiary sarcoma centre allows for optimal management of these patients. To determine the clinicopathological and survival outcomes of patients of chondrosarcoma, we report a total of 20 cases in the last 10 years at our institution. Our results have shown that chondrosarcomas occurred in different age groups and most common location was in axial skeleton. Most common histological type was conventional chondrosarcoma and majority were high grade tumors. All patients had undergone surgery and majority of the patients were alive after many years of treatment with an overall survival of 85%. Long term survival of patients is attributed to completeness of surgical resection.